2022
DOI: 10.1186/s12894-022-01171-9
|View full text |Cite
|
Sign up to set email alerts
|

Urinary incontinence and related quality of life among elderly women in Tabas, South Khorasan, Iran

Abstract: Background Urinary incontinence (UI) is one of the most common problems in old age that is often seen in women, which causes not only physical problems but also psychological, social, economic problems and poor quality of life. The aim of the present study was to evaluate the UI and related quality of life (QoL) in elderly women. Methods This cross-sectional study enrolled 369 women over 60 years old and living in Tabas city, Iran who were selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…This study found lower mean values of lower limb and upper limb strength in women with UI (9.41±3.26 and 18.64±4.97, respectively) compared to women without UI (10.26±3.73 and 20.23±4.88, respectively), along with a higher prevalence of dynapenia in women with UI compared to those without UI (20.88% versus 35.89%). 15,16 Several studies demonstrate important correlations between urinary incontinence, such as poorer perception of quality of life, BMI above (overweight) or below (undernutrition) average, hypertension, use of certain medications, and urogynecological and obstetric histories. 17 However, few studies focus on relating dynapenia, or even the capacity to produce force, with this phenomenon.…”
Section: Relation Dynapenia X Urinary Incontinencementioning
confidence: 99%
“…This study found lower mean values of lower limb and upper limb strength in women with UI (9.41±3.26 and 18.64±4.97, respectively) compared to women without UI (10.26±3.73 and 20.23±4.88, respectively), along with a higher prevalence of dynapenia in women with UI compared to those without UI (20.88% versus 35.89%). 15,16 Several studies demonstrate important correlations between urinary incontinence, such as poorer perception of quality of life, BMI above (overweight) or below (undernutrition) average, hypertension, use of certain medications, and urogynecological and obstetric histories. 17 However, few studies focus on relating dynapenia, or even the capacity to produce force, with this phenomenon.…”
Section: Relation Dynapenia X Urinary Incontinencementioning
confidence: 99%
“…Subsequently, UI is perhaps of the most well-known disorder in advanced age, and contingent upon various populaces, its predominance has been accounted for between 2.8% in Nigeria and 57.7% in Iran 1 The World health organization (WHO) has distinguished the UI as one of the needs in the wellbeing field as effects the personal satisfaction of more seasoned individuals since it influences various parts of life and prompts mental, physical, and social outcomes. Negative mental impacts of UI incorporate uneasiness, stress, disappointment, strain and stress, terrible attitude, low confidence, and fearlessness 2 The commonness of melancholy and uneasiness among individuals with UI is accounted for to be around 20-40% and 56%, separately. As per past examinations, the UI commonness among more seasoned grown-ups has been assessed somewhere in the range of 30 and 70% 3 .…”
Section: Introductionmentioning
confidence: 99%